Education and New Developments 2020 2020
DOI: 10.36315/2020end058
|View full text |Cite
|
Sign up to set email alerts
|

Children With Vision Impairment and Multiple Disabilities: Issues of Communication Skills and Professionals’ Challenges

Abstract: People with vision impairment and multiple disabilities (MDVI) constitute a population with an enormous heterogeneity due to the combination of various disabilities. Education of children with MDVI concerns different domains and it is considered one of the most demanding fields in Special Education as each student with MDVI has different needs and entails unique educational challenges. In specific, the development of communication skills of children with MDVI is a fundamental domain of their education which af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
2
0
3
Order By: Relevance
“…All the professionals have indicated that they found in the manual reflection-based assignments, tasks and examples that have guided them through their learning process. The chapters of the training manual were designed to support the specialists in their learning process about communication strategies and resources for the children with MDVI and also to offer these professionals the opportunity to plan supervised specific interventions for the MDVI children in their praxis (Argyropoulos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…All the professionals have indicated that they found in the manual reflection-based assignments, tasks and examples that have guided them through their learning process. The chapters of the training manual were designed to support the specialists in their learning process about communication strategies and resources for the children with MDVI and also to offer these professionals the opportunity to plan supervised specific interventions for the MDVI children in their praxis (Argyropoulos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…global, populasi keseluruhan penyandang tunanetra terdiri dari penyandang disabilitas netra ganda/multiple disability with visual impairment/MDVI dengan variasi angka antara 30% dan 70% (Kyriacou et al, 2015). Penyandang disabilitas netra ganda diketahui sebagai bagian penyandang disabilitas dengan populasi heterogen dengan kombinasi disabilitas yang kompleks (Argyropoulos et al, 2020). Kondisi tersebut mengakibatkan sering terjadi keterlambatan perkembangan dan kesulitan pada anak tunanetra dan disabilitas ganda.…”
Section: Secaraunclassified
“…Sebagian besar program intervensi penyandang disabilitas ganda didasarkan pada komunikasi yang bertujuan untuk mengonsolidasikan dan memajukan kompetensi komunikasi. Faktanya, seringkali pembelajaran keterampilan komunikasi bagi penyandang disabilitas ganda yang dilakukan di sekolah hanya berfokus pada anak (Argyropoulos et al, 2020). Program pembelajaran dirancang lebih banyak berfokus pada siswa untuk mencapai tujuan pembelajaran yang diinginkan.…”
Section: Secaraunclassified
See 1 more Smart Citation
“…Data collected from the observation were recorded in the field notes. In qualitative methodology, field notes are used for documenting contextual information [24]. Moreover, information gathered in the field can be used to analyze the current situation and triangulate with the information reported on social media.…”
Section: Observationmentioning
confidence: 99%